Master of Group Work Organization Inventory: Possibilities and Limitations - Тахир Ю. Базаров; Александр В. Райков; Ринат Р. Шайхутдинов (Rossijskij psihologičeskij žurnal., 2020)
Introduction. The concept of three roles of the organizer of group work (facilitator, mediator, and moderator) underlies the FaMeMo Inventory, which expands our understanding of the psychology of leadership. This study aims at developing and testing a modified version of the Inventory, which provides an external evaluation of the leader’s competencies by members of his/her group. Methods. We tested the Inventory in a quasi-experiment and examined how the components of the organizer’s competence influence the efficiency of joint intellectual activity. To check the validity of the modified version of the tool we used the following questionnaires: Diagnostics of Group Motivation (I. D. Ladanov), Diagnostics of a Team’s Business, Creative, and Moral Climate (N. P. Fetiskin, V. V. Kozlov, G. M. Manuylov), Technique for Assessing Psychological Atmosphere in a Team (A. F. Fidler), Technique for Determining the Group Cohesion Index (K. I. Sishor), and Technique for Studying the Subject-activity and Socio-psychological Cohesion of a Group (A. V. Sidorenkov, A. L. Mondrus). Results. The results of the empirical study in a sample of 97 individual participants aged 18–25 years indicate the normality in the distribution for the ‘mediator’ scale, the negative asymmetry for the ‘facilitator’ and ‘moderator’ scales, and a high degree of internal consistency reliability of the Inventory scales (0.846–0.854). Structural modeling provided evidence for the factor validity of the Inventory. We identified and analyzed the items that reduced psychometric characteristics and proposed their reformulations. The hypotheses of the convergent validity of the Inventory scales were verified and mainly confirmed. Discussion. The proposed version of the technique demonstrated good psychometric properties, which determines the possibility of investigating competence components in masters of group work organization by means of external evaluation of their group members and also prospects of further development of the tool.